Źródła kultury ceramiki sznurowej ze stanowiska 23 w Czelinie w świetle problematyki wyposażenia grobów ze schyłku neolitu i początku epoki brązu nad dolną Odrą - Kowalski, Krzysztof; Matuszewska, Agnieszka (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
Accidental discoveries of artifacts – a clay pegged cup decorated with cord impressions and a stone hatchet of the Corded Ware culture at site 23 in Czelin (Mieszkowice commune, west-Pomeranian voivodeship), previously published, a damaged multi-burial grave of the TRB culture (g. 1), became the groundwork for the recapitulation of problems connected with the grave goods from the late Neolithic and the start of the Bronze Age on the lower Oder. In connection with the lack of evidence of these unknown sources, the authors attempt to ascertain a link with the damaged grave – the only recognized feature of the Corded Ware culture from the site at Czelin. Examples from late Neolithic and early Bronze age sepulchral discoveries in the area of the lower Oder, show that problems similar to those from Czelin also occurred, concerning the lack of evidence for funerary rituals. In Czelin a small part of a grave pit survived, from which the incomplete remains of three burials were excavated: of a maturus female (40–45 years old), for whom an incomplete genetic prole has been made, an infans II child and an adult. The grave in situ contained only a clay vessel – an S-shaped pegged cup, decorated with cord impressions (g. 2). A radiocarbon date was obtained from the female skeleton – 3785±35 BP (calibration: 1ä 2290BC (47.1%) 2190BC; 2ä 2340BC (91.5%) 2120BC), which confirmed a great convergence of the chronology of the grave from Czelin with a multi-burial grave from Dębogóra (Widuchowa commune, West Pomeranian voivodeship), noted on the grounds of the similarity of cups discovered in both sepulchral features. These discoveries may be placed in stage 3a of the Corded Ware culture of the lower Oder group of this culture’s period, which is identified with a horizon of regional differentiation of cultural inventories and input of local corded societies into a sphere of contacts with proto- and early Bronze Age societies. A similar chronological position may be accorded to a cup discovered at site 23 in Czelin in unknown circumstances (g. 3). It shows a strong typological similarity with the cup discovered in the grave but differs in its size (g. 5). There is less data concerning the stone hatchet, which disappeared and is known only from a photo (g. 4). Only generally it may be connected with younger or degenerated types of series K, possibly hatchets of the Wkra type that begin to appear in graves in stage 2 of the Corded Ware culture. In all known burials connected with the Corded Ware culture in the Oder estuary the presence of grave gifts was stated. Most frequently pottery occurred (table 1) in the form of 1–2 vessels although other specimens were deposited (6–7 items). The second frequent group of artifacts includes stone hatchets (from 1 to 4 types in a grave), most often of the Wkra type or hatchets of type K. The last numerously represented category comprises int axes. Slightly rarer are int arrowheads, flint daggers, as well as other stone products (axes, grinders, fragments of a stone quern) and int ones (blades, chisels, a sickle). In just four graves amber constituted part of the gifts. Moreover, in one case a bone blade and a clay whorl were recorded. The present state of knowledge considerably limits our understanding about correlation between the dead sex and types of burial gifts, which is often undertaken in different regions. In collective burials no clear growth in the number of grave goods was observed. The most interesting case, in comparison with Czelin, was a grave from Dêbogórza, where each of the individuals was buried with one vessel. Within the whole Corded Ware culture circle there is no uniform practice concerning the number and character of burial gifts deposited in graves. Most often such artifacts as stone hatchets, axes, chisels or stone knives are associated with male graves, whereas among females, ornaments (mostly made of amber) and pottery vessels are mentioned. Children may have had no accompanying goods or could be equipped with pottery, hatchets, and sometimes miniaturized artifacts, including vessels. Looking at the collected information it seems that a connection of incidental nds of the clay cup and stone hatchet, which was discovered at the Czelin multi-burial grave cannot be excluded.